Implementación de una máquina expendedora de internet y su incidencia en el área educativa del Colegio Particular Mixto Padre Marcos Benetazzo del cantón Babahoyo de la Provincia de Los Ríos durante el periodo 2019 - Haz Rumazo, Jonathan Antonio (2019)
This research work aims to implement an internet vending machine and its impact on the educational area of the Father Marcos Benetazzo Mixed Private School of the Babahoyo Canton of the Province of Los Ríos during the 2019 period. In the development of the research the deductive and inductive method was used, the techniques that were implemented were surveys through instruments such as a questionnaire of questions to gather information which was addressed to the teachers and students of the Mixed Private School Father Marcos Benetazzo taking A sample of 257 people to develop graphic tables for the respective analysis. The research was developed through scientific methods that allowed to describe in detail and punctuate the different situations of the institution and what entails the implementation of a useful tool for a better academic development.